PEMBIAYAAN PENDIDIKAN DASAR DAN PERMASALAHANNYA - Ananda, Rizki; Pajriani, Laila; Rahmadani, Suci Akfiza; Wahyuni, Zakkia; Alamsah, Ahmad Zikri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Financing basic education is a crucial element in ensuring equitable access to and quality of education in Indonesia. Although the government has allocated funds through various schemes such as the School Operational Assistance (BOS) and Special Allocation Funds (DAK), several challenges remain—ranging from distribution issues and inefficient budget use to a lack of transparency in fund management. This article provides a comprehensive overview of the sources of basic education funding, allocation mechanisms, and obstacles encountered in implementation. It also discusses the roles of stakeholders and offers policy recommendations aimed at improving the efficiency and equity of basic education financing in Indonesia.